2016
DOI: 10.1038/srep20497
|View full text |Cite
|
Sign up to set email alerts
|

Fenestrated and Chimney Technique for Juxtarenal Aortic Aneurysm: A Systematic Review and Pooled Data Analysis

Abstract: Juxtarenal aortic aneurysms (JAA) account for approximately 15% of abdominal aortic aneurysms. Fenestrated endovascular aneurysm repair (FEVAR) and chimney endovascular aneurysm repair (CH-EVAR) are both effective methods to treat JAAs, but the comparative effectiveness of these treatment modalities is unclear. We searched the PubMed, Medline, Embase, and Cochrane databases to identify English language articles published between January 2005 and September 2013 on management of JAA with fenestrated and chimney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 42 publications
1
38
0
5
Order By: Relevance
“…24,25 Rates of secondary endovascular interventions after chEVAR have a wider range but on average are similar. 5,26,27 There were no conversions to open repair after ESAR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Rates of secondary endovascular interventions after chEVAR have a wider range but on average are similar. 5,26,27 There were no conversions to open repair after ESAR.…”
Section: Discussionmentioning
confidence: 99%
“…Total fluoroscopy time to complete ESAR averaged 35.3 minutes, with a mean duration of implant procedure of 148 minutes. A meta-analysis of fEVAR and chEVAR by Li et al 26 found that procedure length averaged 261 minutes for fEVAR and 178 minutes for chEVAR. Implantation of EndoAnchor implants on average required an additional 17 minutes to complete, an insignificant increase in total operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Although endovascular options provide a less invasive approach and more favourable outcomes than open surgery in the management of TAAAs, more than 30% of patients are not suitable for conventional endovascular repair because of anatomic constraints around the proximal neck. 7 However, a number of endovascular techniques and devices have been developed to bypass these challenges. These include, branched, fenestrated and chimney stent graft techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The chimney technique involves the use of off-the-shelf covered stents placed between the main body graft and the aortic wall to facilitate perfusion of the renal arteries. Chimney stenting has been shown to have higher mortality and have a higher incidence of renal impairment when compared with fenestrated EVAR; however, it is typically performed in more urgent cases 4. Physician-modified stent grafts involve the partial deployment of the stent graft, creation of the appropriate fenestrations and resheathing of the stent graft prior to the deployment within the patient.…”
Section: Discussionmentioning
confidence: 99%